Cover Picture: Transition‐Metal‐Free Decarboxylative Coupling Reactions for the Synthesis of Propargyl Alcohols (Asian J. Org. Chem. 9/2016). Issue 9 (8th September 2016) - Irudayanathan, Francis Mariaraj; Kim, Jimin; Song, Kwang Ho; Lee, Sunwoo
Abstract : Propargyl alcohols have been synthesized through a transition‐metal‐free decarboxylative coupling reaction . Aryl propiolic acids were treated with aldehyde (or ketone) in the presence of Cs2 CO3 to afford the corresponding propargyl alcohols in moderate‐to‐good yields. In particular, the reaction with 2, 2, 2‐trifluoroacetophenone afforded the trifluoromethylated propargyl alcohols in good yields. More information can be found in the full paper by S. Lee and co‐workers onpage 1148 in Issue 9, 2016 (DOI:10.1002/ajoc.201600265 ).